A systematic review of 3-D printing in cardiovascular and cerebrovascular diseases - Sun, Zhonghua; Shen-Yuan, L. (Turkish Society of Cardiology, 2017)
Objective: The application of 3-D printing has been increasingly used in medicine, with research showing many applications in cardiovascular disease. This systematic review analyzes those studies published about the applications of 3-D printed, patient-specific models in cardiovascular and cerebrovascular diseases. Methods: A search of PubMed/Medline and Scopus databases was performed to identify studies investigating the 3-D printing in cardiovascular and cerebrovascular diseases. Only studies based on patient’s medical images were eligible for review, while reports on in vitro phantom or review articles were excluded. Results: A total of 48 studies met selection criteria for inclusion in the review. A range of patient-specific 3-D printed models of different cardiovascular and cerebrovascular diseases were generated in these studies with most of them being developed using cardiac CT and MRI data, less commonly with 3-D invasive angiographic or echocardiographic images. The review of these studies showed high accuracy of 3-D printed, patient-specific models to represent complex anatomy of the cardiovascular and cerebrovascular system and depict various abnormalities, especially congenital heart diseases and valvular pathologies. Further, 3-D printing can serve as a useful education tool for both parents and clinicians, and a valuable tool for pre-surgical planning and simulation. Conclusion: This systematic review shows that 3-D printed models based on medical imaging modalities can accurately replicate complex anatomical structures and pathologies of the cardiovascular and cerebrovascular system. 3-D printing is a useful tool for both education and surgical planning in these diseases.